Perencanaan Penataan Lahan Reklamasi Dan Revegetasi pada Kegiatan Pertambangan Batu Andesit Di Pt. Toha Batu Palu: PERENCANAAN PENATAAN LAHAN REKLAMASI DAN REVEGETASI PADA KEGIATAN PERTAMBANGAN BATU ANDESIT DI PT. TOHA BATU PALU - Fairus Atika Redanto Putri; Mangesa Albert Takin; Kusdarini Esthi (Jurnal Teknologi Lingkungan, 2025)
Andesite mining activities at PT. Toha Batu Palu has significant environmental impacts, including land degradation, vegetation loss, and potential erosion. This study aimed to plan land reclamation and revegetation in the former mining area as an environmental restoration effort. Researchers used primary and secondary data collection methods, data processing to calculate overburden and topsoil requirements, and planned the types and quantities of plants to be planted. Land reclamation was carried out over 3.5 hectares using a leveling system and spreading 30 cm of topsoil. The company carried out revegetation activities by planting pioneer plants (sengon), ground cover plants (Kacang Lcc CP), and intercropping plants (kayu jawa), which are highly adaptable to the climate conditions of Palu. The results of this study indicated that the planned reclamation and revegetation could reduce environmental impacts and serve as a reference for the company in managing post-mining areas sustainably.